Association between days to complete inpatient discharge summaries with all‐payer hospital readmissions in Maryland. Issue 6 (23rd February 2016) - Hoyer, Erik H.; Odonkor, Charles A.; Bhatia, Sumit N.; Leung, Curtis; Deutschendorf, Amy; Brotman, Daniel J.
Abstract : OBJECTIVE: Hospital discharge summaries can provide valuable information to future providers and may help to prevent hospital readmissions. We sought to examine whether the number of days to complete hospital discharge summaries is associated with 30‐day readmission rate. PATIENTS AND METHODS: This was a retrospective cohort study conducted on 87, 994 consecutive discharges between January 1, 2013 and December 31, 2014, in a large urban academic hospital. We used multivariable logistic regression models to examine the association between days to complete the discharge summary and hospital readmissions while controlling for age, gender, race, payer, hospital service (gynecology–obstetrics, medicine, neurosciences, oncology, pediatrics, and surgical sciences), discharge location, length of stay, expected readmission rate in Maryland based on diagnosis and illness severity, and the Agency for Healthcare Research and Quality Comorbidity Index. Days to complete the hospital discharge summary—the primary exposure variable—was assessed using the 20th percentile (>3 vs ≤3 days) and as a continuous variable (odds ratio expressed per 3‐day increase). The main outcome was all‐cause readmission to any acute care hospital in Maryland within 30 days. RESULTS: Among the 87, 994 patients, there were 14, 248 (16.2%) total readmissions. Discharge summary completion >3 days was significantly associated with readmission, with adjusted odds ratio (OR) (95% confidence interval [CI]) of 1.09 (1.04 to 1.13, P = 0.001). We also found that every additional 3 days to complete the discharge summary was associated with an increased adjusted odds of readmission by 1% (OR: 1.01, 95% CI: 1.00 to 1.01, P < 0.001). CONCLUSION: Longer days to complete discharge summaries were associated with higher rates of all‐cause hospital readmissions. Timely discharge summary completion time may be a quality indicator to evaluate current practice and as a potential strategy to improve patient outcomes. Journal of Hospital Medicine 2016;11:393–400. 2016 Society of Hospital Medicine